Colonization, Succession and Preference for Tree Portion by Insects on Felled West Himalayan Spruce, Picea smithiana - Singh, Arun P.; Bhandari, R. S. (Indian Forester, 1997)
Studies on colonization, succession and preference for tree portion by insects were carried out on felled trees of spruce, Picea smithiana trees. A total of 14 species of insects colonized the felled trees. Two species are important wood boring beetles, Tetropium oreinum and Dryocotes indicus which infest freshly felled trees. A sap/fluid feeding bug Mezira tenuicornis also feeds on the tree till the 3rd year followed by a decaying wood boring fly, Eristalis tenox in the 4th year after felling. Five species of predatory beetles were also collected. Thanasimus himalayensis, predating on T. oreinum and D.indicus; Ampedu spp. And Cucujus bicolor predating on D. indicus along with a brenthid and carabid species that are also predatory beetles. Archotermopsis wroughtonii a dead wood termite and a predatory carabid beetle colonize the tree from 5-8 years after felling. However, from 18 to 22 years after felling, 3 species of beetles that are borers of rotten wood, Hemisodrocus nepalensis, Oryctes nasicornis and Blaps socia feed on spruce. Preference for the tree portion by insects showed that during the first 2 years after felling all the three portions of the tree are colonized i.e. bottom, middle and top. While from 3 to 8 years the bottom and middle portions are inhabited by insects. However, from 18 to 22 years after felling insects infest the bottom portion of the tree.